PALEOZOIC NORTHWARD DRIFT OF THE NORTH TIEN SHAN (CENTRAL ASIA) AS REVEALED BY ORDOVICIAN AND CARBONIFEROUS PALEOMAGNETISM - Bazhenov M.L.; Degtyarev K.E.; Levashova N.M.; Collins A.Q.; Van der Voo R.; Mikolaichuk A.V.; Pavlov V.E. (My University, 2003)
Three new Middle–Late Ordovician and two new Early Carboniferous paleomagnetic poles have been obtained from the North Tien Shan Zone (NTZ) of the Ural–Mongol belt in Kyrgyzstan and Kazakhstan. Paleolatitudes for the Carboniferous are unambiguously northerly and average 15.5°N, whereas the Ordovician paleolatitudes (6°, 9°, and 9°) are inferred to be southerly, given that a very large (∼180°) rotation of the NTZ would be necessary during the middle Paleozoic if the other polarity option was chosen. Thus, the NTZ drifted northward during much of the Paleozoic; east–west drift cannot be determined, as is well known, from paleomagnetic data. In addition, detailed thermal demagnetization analysis reveals two overprints, one of recent age and the other of Permian age, which is a time of strong deformation in the NTZ. The paleolatitude of the combined Permian overprint is 30.5+2°N. The paleolatitudes collectively track those predicted for the area by extrapolation from Baltica very well, but are different from those of Siberia for Ordovician times. This finding is compatible with Sengör and Natal'in's [Sengör, A.M.C., Natal'in, B.A., 1996. Paleotectonics of Asia: fragments of a synthesis. In: Yin A., Harrison, M. (Eds.), The Tectonic Evolution of Asia. Cambridge Univ. Press, Cambridge, pp. 486–640] model of tectonic evolution of the Ural–Mongol belt and disagrees with the models of other researchers. Declinations of the Ordovician and Early Carboniferous results range from northwesterly to northeasterly, and are clearly affected by local relative rotations, which seem characteristic for the entire NTZ, because the Permian overprint declinations also show such a spread. Apparently, the important latest Paleozoic–Triassic deformation involved shear zone-related rotations as well as folding and significant granitic intrusions.
Keywords: Tien Shan; Carboniferous; Paleolatitudes; Ural–Mongol fold belt; Paleopoles; Ordovician; Paleozoic::Carboniferous; Paleozoic::Ordovician; Палеозой::Ордовикская; Палеозой::Каменноугольная